Study on Forming Mechanism of Condensate Film of Steam-gas Mixed Fluid - Li Huijun; Guan Xiuhong; Gao Lisha (Zhileng xuebao)
In the condensation heat transfer process of steam-gas mixed fluid, the liquid film formed by the condensation has a great effect to heat transfer; so the discussion of the changes of the liquid film thickness along the wall was conducive to the enhancement of heat transfer. The mechanism of steam condensation of mixed fluid, the distribution of liquid film along the wall and the heat transfer performance were analyzed, and appropriate physical and mathematical models were established. With the given initial conditions, the results of the calculation indicate that the thickness of the liquid film was gradually increased along the wall flowing down and the heat transfer performance gradually reduces; meanwhile the effects of tube wall temperature, vapor-gas mixed fluid velocity and tube diameter on the liquid film formation and the heat transfer performance were analyzed, which provided a theoretical basis for the enhancement of condensation heat transfer process.